KERENTAAN PENDUDUK USIA LANJUT Dl JAWA-BALI - Tukiran Tukiran (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2007)
Most elderly have lower education level, they work in agriculture sector with lower income so it is natural if they are categorized as vulnerable in meeting their basic needs. They are willing to work anything, they depend on the fund giving by their children and children in laws as long as they have income. This depency is higher on elderly women than men. When they get sick, they only go to puskesmas or pustu to find the cure. They spend most of their time watching television even most of the programs are not suitable to their needs. The government has done many programs in helping there vulnerable citizens, but still these elderly have not catch their attention yet.